2021
DOI: 10.3390/metabo11030169
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Levels of Metabolic Predictors of Coronary Heart Disease between Healthy Lean and Overweight Females

Abstract: Screening for the metabolomic signature of coronary heart disease (CHD) before disease onset could help in early diagnosis and potentially disease prevention. In this study, the levels of 17 CHD metabolic biomarkers in apparently healthy overweight females were compared to lean counterparts, and their associations with conventional clinical risk factors were determined. Clinical and metabolic data from 200 apparently healthy non-obese Qatari females were collected from Qatar Biobank (discovery cohort). Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Alpha-linolenic acid is an essential omega-3 fatty acid highly present in edible and flaxseed oils ( 29 ), while gamma-linolenic acid is an omega-6 fatty acid, abundant in green leafy vegetables and nuts ( 45 ). Similar to our findings, a study comparing levels of metabolic predictors of coronary heart disease indicated that linolenate (18:3n3 or 6) was significantly different between lean and overweight females and was associated with elevated c-peptide and diastolic blood pressure ( 46 ). Zhe Wang et al also reported that linoleante is associated with increased risk of coronary heart disease ( 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…Alpha-linolenic acid is an essential omega-3 fatty acid highly present in edible and flaxseed oils ( 29 ), while gamma-linolenic acid is an omega-6 fatty acid, abundant in green leafy vegetables and nuts ( 45 ). Similar to our findings, a study comparing levels of metabolic predictors of coronary heart disease indicated that linolenate (18:3n3 or 6) was significantly different between lean and overweight females and was associated with elevated c-peptide and diastolic blood pressure ( 46 ). Zhe Wang et al also reported that linoleante is associated with increased risk of coronary heart disease ( 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, several studies are designed to provide the genomic or metabolomic background of CHD ( 35 37 ). All these studies, once combined together, might provide essential evidence for the efficient risk-stratification of patients with CHD.…”
Section: Discussionmentioning
confidence: 99%